2023
DOI: 10.1002/lary.30684
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Septoplasty in Patients with Nasal Obstruction: A Systematic Review and Meta‐analysis

Abstract: ObjectiveSeptoplasty is the most frequently performed ENT surgery to correct nasal septal deviation (NSD). The present study aimed to quantify the effectiveness of septoplasty with or without turbinate surgery according to NOSE questionnaire scores, with the hypothesis that it is able to clinically improve patient‐reported nasal obstructive symptoms in the post‐operative follow‐up.MethodsAn electronic search was performed on PubMed/MEDLINE, Embase, and Cochrane Library. The primary outcome was the change in NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Many studies have shown that septoplasty with or without turbinoplasty is effective in improving symptoms of nasal obstruction, especially when compared to nonsurgical medical treatment. [8][9][10][11] However, most of these studies and nearly all current reviews focus primarily on short-term (<12 months) outcomes. Whether or not these high septoplasty success rates persist years after surgery remains unanswered, as some long-term studies suggest that patient symptoms may worsen again over time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that septoplasty with or without turbinoplasty is effective in improving symptoms of nasal obstruction, especially when compared to nonsurgical medical treatment. [8][9][10][11] However, most of these studies and nearly all current reviews focus primarily on short-term (<12 months) outcomes. Whether or not these high septoplasty success rates persist years after surgery remains unanswered, as some long-term studies suggest that patient symptoms may worsen again over time.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that septoplasty with or without turbinoplasty is effective in improving symptoms of nasal obstruction, especially when compared to nonsurgical medical treatment 8–11 . However, most of these studies and nearly all current reviews focus primarily on short‐term (<12 months) outcomes.…”
Section: Introductionmentioning
confidence: 99%